Regulatory T Cells: An Emerging Player in Radiation-Induced Lung Injury - Guo, Tiantian; Zou, Liqing; Ni, Jianjiao; Zhou, Yue; Ye, Luxi; Yang, Xi; Zhu, Zhengfei (Frontiers in Immunology, 2020)
Regulatory T cells (Tregs), which have long been recognized as essential regulators of both inflammation and autoimmunity, also impede effective antitumor immune response due to their immunosuppressive properties. Combined radiotherapy and immunotherapeutic interventions focusing on the removal of Tregs have recently garnered interest as a promising strategy to reverse immunosuppression. Meanwhile, Tregs are emerging as a key player in the pathogenesis of radiation-induced lung injury (RILI), a frequent and potentially life-threatening complication of thoracic radiotherapy. Recognition of the critical role of Tregs in RILI raises the important question of whether radiotherapy combined with Treg-targeting immunotherapy offers any beneficial effects in the protection of normal lung tissue. This present review focuses on the contributions of Tregs to RILI, with particular emphasis on the suspected differential role of Tregs in the pneumonitic phase and fibrotic phase of RILI. We also introduce recent progress on the potential mechanisms by which Tregs modulate RILI and the crosstalk among Tregs, other infiltrating T cells, fibrocytes, and resident epithelial cells driving disease pathogenesis. Finally, we discuss whether Tregs also hold promise as a potential target for immunotherapeutic interventions for RILI.